PENGARUH VARIASI KONSENTRASI AMILUM JANTUNG PISANG BATU SEBAGAI BAHAN PENGIKAT TERHADAP SIFAT FISIK TABLET ASAM ASETIL SALISILAT - Sinaga, Alex; Manalu, Adelya I (JIFI (Jurnal Ilmiah Farmasi Imelda), 2021)
Tablet dosage form is one of the most widely used pharmaceutical. Acetyl salicylic acid is an anti inflammatory medicine, active substance not heat resistant. Starch as a binder of materials in the manufacture of tablets are hydrophilic because amylopectin starch can absorb most of the water. This study aims to determine the variation of the concentration of starch banana heart of stone as the material of binder on physico-chemical properties acid tablets acetyl salicylic meet the requirements of the Indonesian Pharmacopoeia. Based on the explanation above, the research conducted to make four concentration of the starch of banana, i.e. FI (5%), FII (10%), FIII (12.5%) and FIV (15%). From the results evaluation obtained include : flow time, steep angle, indication index, uniformity of weight, hardness, fragility and crumbling time of tablets, all formulas have been qualified by Pharmacopoeia Indonesia. Formulation IV after investigation had better tablet quality.